Green light–emitting diodes with high efficiency organosilane-functionalized carbon dots. Issue 181 (13th June 2017) - Wang, Kai; Yin, Zhengmao; Du, Fanglin
ABSTRACT: Organosilane-functionalized carbon dots (SiCDs) with green emission were prepared by one-step solvothermal method. Anhydrous citric acid and N-(2-aminoethyl)-3-aminopropyltrimethoxy-silane (KH792) were used for the preparation of SiCDs. Green light-emitting diodes (LEDs) were fabricated by combination of a 450 nm-emitting blue LED chips and green SiCDs, since green SiCDs was used to convert blue light to green light. The luminous efficiency of green LEDs can reach 60.96 lm/W. The as-prepared polymerizable SiCDs are hopeful to provide new opportunity to simplify the preparation process and improve optical performances of green LEDs.